Localization and potential role of prostate microbiota - Okada, Koichi; Takezawa, Kentaro; Tsujimura, Go; Imanaka, Takahiro; Kuribayashi, Sohei; Ueda, Norichika; Hatano, Koji; Fukuhara, Shinichiro; Kiuchi, Hiroshi; Fujita, Kazutoshi; Motooka, Daisuke; Nakamura, Shota; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
We aimed to clarify the presence and localization of the prostate microbiota and examine its association with benign prostate enlargement (BPE). The microbiota of prostate tissues and catheterized urine from 15 patients were analyzed by 16S metagenomic analysis and compared to show that the prostate microbiota was not a contaminant of the urinary microbiota. Fluorescence in situ hybridization (FISH) and in situ hybridization (ISH) using the specific probe for eubacteria was performed on prostate tissue to show the localization of bacteria in the prostate. The BPE group was defined as prostate volume ≥30 mL, and the non-BPE group as prostate volume <30 mL. The microbiota of the two groups were compared to clarify the association between prostate microbiota and BPE. Faith’s phylogenetic diversity index of prostate tissue was significantly higher than that of urine (42.3±3.8 vs 25.5±5.6, P=0.01). Principal coordinate analysis showed a significant difference between the microbiota of prostate tissue and catheterized urine (P<0.01). FISH and ISH showed the presence of bacteria in the prostatic duct. Comparison of prostate microbiota between the BPE and non-BPE groups showed that the Chao1 index of the BPE group was significantly lower than that of the latter [142 (50–316) vs 169 (97–665), P=0.047] and the abundance of Burkholderia was significantly higher in the BPE group than in the latter. We demonstrated that the prostate microbiota was located in the prostatic duct and reduced diversity of prostate microbiota was associated with BPE, suggesting that prostate microbiota plays a role in BPE.